Development of the structure of Hungarian gross electricity production between 2010-2021 - Bozsik, Nándor; Bozsik, Norbert; Tánczos, Tamás (Studia Mundi – Economica, 2023)
The Hungarian electricity production is based on three pillars: fossil, nuclear and renewable energies. While domestic electricity production fell by about 6.5% between 2010 and 2020, gross electricity consumption increased by about 10%, which can be attributed to the decrease in production and the significant increase in electricity imports.   The main reason for the increase in imports is that Hungary can buy cheap electricity from neighboring states. A positive development of the past period is that renewables has been playing an increasingly important role in electricity production. The increase in renewable energy consumption is connected with a decrease in the use of coal and gas, which is in line with EU commitments related to the reduction of greenhouse gas emissions and an important factor in the fight against climate change. In order to reduce the exposure of electricity production and use, it would be important to further expand renewable energies. In our article, we analyzed the structural transformation of Hungarian electricity production for the period between 2010 and 2020, supplemented by forecasts for the year 2021. During the research, we performed correlation calculation and a linear regression analysis, revealing the possible relationships between the energy carriers. The results show that an increase in solar energy production is accompanied by a decrease in coal-based electricity production, while an increase in natural gas-based electricity production is associated with a decrease in net electricity imports.  the coming decades, it will be a serious challenge for Hungary to be able to provide its own electricity needs in a safe, economical and environmentally friendly way.
Keywords: fossil energy; correlation; renewable energy; nuclear energy; electricity generation